Pemanfaatan Lumpur Minyak dengan Solar sebagai Energi Alternatif Bahan Bakar: Utilization of Oil Sludge with Diesel as Fuel Alternative - Yunus Tonapa Sarungu; Rony Pasonang Sihombing (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2021)
Oil sludge resulting from crude oil processing in the petroleum industry could have a negative impact on the environment. Oil sludge could also be classified as hazardous waste and able to damage the environment and human health. Therefore, it was necessary to solve this issues. Oil sludge hydrocarbon utilizing to get higher value was one of solution offered by these research. In the utilization process, filtration method was used at first procedure and followed by diesel mixing at ratio 1:0.1, 1:0.2, 1:0.3, 1:0.4, and 1:0.5. The mixture was then analyzed for several parameters such as heating value, moisture content, ash content, and flashpoint. The results of heating values ranging from 5.966 calories/ gram to 7.210 calories/ gram, the flashpoint was from 38 ⁰C to 76 ⁰C, the water content was from 51.89% to 54.52%, the ash content was from 12.3% to 18.03%. The results showed that utilization of oil sludge could be used as liquid fuel alternative energy. Keywords: oil sludge, energy alternative, liquid fuel